2010
DOI: 10.1086/650001
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of HIV‐1 Drug‐Resistant Variants: Prevalence and Effect on Treatment Outcome

Abstract: We found the prevalence of TDR in recently infected ART-naive patients to be higher than that estimated by ViroSeq genotyping alone. Follow-up of patients after treatment initiation showed a trend toward there being more clinical complications for patients carrying TDR, although a significant effect on treatment outcome could not be demonstrated. Therefore, the clinical relevance of low-abundance resistant quasispecies in early infection is still in question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
66
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 32 publications
10
66
0
Order By: Relevance
“…Using ultrasensitive genotypic assays, many research groups have reported high proportions of transmitted DRM among ART-naïve individuals (15,30,32,37,48,58,65), but these findings are not consistent with the descriptions of mono-or oligoclonal transmission in the env coding region by SGS and UDS (1,19,25,33). The primary goal of this analysis was to investigate whether detected minority viral variants in the earliest part of HIV-1 infection were (i) truly transmitted, (ii) a consequence of viral evolution and selection early after transmission, (iii) technical errors in highly sensitive detection methods, or (iii) de novo mutations resulting as a consequence of the high error rate of HIV-1 replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using ultrasensitive genotypic assays, many research groups have reported high proportions of transmitted DRM among ART-naïve individuals (15,30,32,37,48,58,65), but these findings are not consistent with the descriptions of mono-or oligoclonal transmission in the env coding region by SGS and UDS (1,19,25,33). The primary goal of this analysis was to investigate whether detected minority viral variants in the earliest part of HIV-1 infection were (i) truly transmitted, (ii) a consequence of viral evolution and selection early after transmission, (iii) technical errors in highly sensitive detection methods, or (iii) de novo mutations resulting as a consequence of the high error rate of HIV-1 replication.…”
Section: Discussionmentioning
confidence: 99%
“…It appears, however, to be increasing in these settings as well (2,14,51). Using more-sensitive genotypic assays, different research groups (15,30,32,37,48,58,65) have reported higher proportions of transmitted DRM in ART-naive individuals. The clinical importance of these low-level DRM remains unclear, as they have been associated with clinical consequences in some (21,24,32,36,37,40,46,54,55,63,66,71) but not all (30,47,58) studies.…”
mentioning
confidence: 99%
“…11 The utility of pretherapy testing may be limited by minority HIV-1 variants present in < 20% of the viral population that are not reliably detected by standard sequencing, 12 and that may jeopardize virologic response. [13][14][15][16][17] The prevalence of minority pretherapy drug resistance mutations varies, with estimates based on highly sensitive research assays often double those reported using standard sequence analysis. [14][15][16][17][18][19] Some variation may be related to methods for measuring low abundance resistance mutations.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] The prevalence of minority pretherapy drug resistance mutations varies, with estimates based on highly sensitive research assays often double those reported using standard sequence analysis. [14][15][16][17][18][19] Some variation may be related to methods for measuring low abundance resistance mutations. For example, allele-specific polymerase chain reaction (PCR) detects mutations that make up ‡ 0.01% of the viral population, 15 which would require at least 30,000 input templates for reasonable sampling; however, prevalence estimates are based on a few, predetermined mutations, and estimates of resistance mutations in an individual may be biased by differential amplification.…”
Section: Introductionmentioning
confidence: 99%
“…This inroduction is frequently observed at position 215 of the reverse transcriptase (RT) and can result in the presence of several different amino acids at that position (T215D/E/I/S/V/N/A/L) (3, 14). Once formed, overgrowth of the fitter back-mutated variant may reduce the originally infecting variant to a level that is no longer detectable by population sequencing but that may be picked up by more-sensitive techniques, such as deep sequencing or allele-specific PCR, because these methods permit reliable detection of variants occupying 1% or less of the viral population (15)(16)(17)(18)(19)(20)(21)(22)(23)(24).It has been shown that resistant virus acquired at the time of primary infection massively fuels the cellular reservoir and persists there for a very long time (25). Sequencing of proviral DNA, therefore, seems to be an attractive substitute for RNA sequencing because it may increase the chance to identify the originally infecting virus.…”
mentioning
confidence: 99%